Suction Feeding in Dendropsophus cerradensis Tadpoles: New Behavioral Observations and Morphological Traits in a Member of the D. microcephalus Group (Anura, Hylidae) - Marcondes, Barbara Caroline; dos Santos Dias, Pedro Henrique; Araújo, Raíla Brena; de Lima, Guilherme Castro Franco [UNESP]; Cuervo‐Santos, Caroline [UNESP]; Oswald, Caroline Batistim; Magalhães, Rafael Felix; Taboga, Sebastião Roberto [UNESP]; Pezzuti, Tiago Leite [UNESP] (Wiley, 2025)
We present, for the first time, the suction feeding behavior of the tadpole of Dendropsophus cerradensis (Hylidae, Dendropsophini), along with a detailed description of its external morphology, buccopharyngeal cavity, and musculoskeletal system. The tadpole exhibits a depressed body, anteriorly positioned nostrils, a modified oral disc (completely covered by external folds), and a low tail, resembling other members of the D. microcephalus group. The buccopharyngeal cavity is reduced in features, with internal nares positioned at an acute angle and covered by prenarial papillae, exclusive for this species. Muscle insertion patterns are generally consistent with other Dendropsophini tadpoles, except for the insertion of the m. levator mandibulae longus profundus on Meckel's cartilage. The feeding behavior is characterized by the use of an oral tube that protrudes exclusively during predation. This mechanism may be associated with robust mandibular and hyoid musculature, as well as a modified cranial structure-including a unique suprarostral element, quadrangular muscular processes, robust ceratohyals, and a reduced branchial basket in the hyobranchial skeleton-which enables fast suction movements. This study presents a previously unknown aspect of the protractile oral tube and feeding behavior of the D. microcephalus group, providing new insights into the morphology and feeding behavior of the group.